THE RESULTS OF THE STUDY OF ACUTE TOXICITY OF THE FOOD MIXTURE «MELLA CROISSANT» - Sherkuziev, G.F.; Khegai, L.N.; Samigova, N.R.; Azizova, F.L.; Kurbanova, Sh.I. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To study acute toxicity and determine its class in the intragastric route of intake of the food mixture “Mella croissant” Material and methods: Experiments on the acute toxicity of the food mixture “Mella croissant” were carried out on 2 groups of animals: group 1 (experimental) – 6 white rats weighing 150-165 g. The prepared suspension of the food mixture “Mella croissant” was administered once intragastrically at the rate of 4.71 ml/100 g (dose equivalent of 5000 mg/kg). 6 animals of the 2nd group, which served as a control, received distilled water. Results: food supplement “Mella croissant” according to the parameters of acute toxicity during the intragastric route of entry belongs to class 4 (low toxicity substance). Conclusions: The studied food mixture does not have a local irritant effect on the skin, the properties of material and functional cumulation in the recommended dose of 413 mg/kg.